1983
DOI: 10.1002/jmv.1890120406
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus‐specific IgM antibodies in sera from patients with chronic active hepatitis

Abstract: The occurrence of measles virus-specific IgM antibodies in sera from patients with chronic active hepatitis not caused by Hepatitis B virus was examined by a specific enzyme-linked immunosorbent assay (ELISA). Using whole serum, specific IgM antibodies were detected in 12 of 23 sera from patients with hepatitis B surface antigen (HBsAg)-negative chronic active hepatitis. In nine of these sera the finding of specific IgM antibodies was verified by separation of IgM by density gradient centrifugation and examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Infections with hepatitis A virus[120-125], hepatitis B virus (HBV)[126], hepatitis C virus (HCV)[127], Epstein-Barr virus (EBV)[128-132], varicella zoster[133], and human immunodeficiency virus[134] have been proposed as triggering events (Table 2). Other studies have described evidence of HCV[135-139], measles virus[140-142], cytomegalovirus (CMV)[143], and EBV[144] in the serum or liver tissue of patients with autoimmune hepatitis. These findings have supported an association between viral infection and autoimmune hepatitis, but the nature of the relationship (coincidental vs etiologic) has been uncertain[145,146].…”
Section: Triggering Eventsmentioning
confidence: 99%
“…Infections with hepatitis A virus[120-125], hepatitis B virus (HBV)[126], hepatitis C virus (HCV)[127], Epstein-Barr virus (EBV)[128-132], varicella zoster[133], and human immunodeficiency virus[134] have been proposed as triggering events (Table 2). Other studies have described evidence of HCV[135-139], measles virus[140-142], cytomegalovirus (CMV)[143], and EBV[144] in the serum or liver tissue of patients with autoimmune hepatitis. These findings have supported an association between viral infection and autoimmune hepatitis, but the nature of the relationship (coincidental vs etiologic) has been uncertain[145,146].…”
Section: Triggering Eventsmentioning
confidence: 99%
“…In 1980's IgM antibodies to measles virus (MS) have been found in 12 of 23 patients with AIH [77]. In another study, around the same time the MV genome has been found to persist in 12 of 18 AIH patients [78].…”
Section: Other Pathogensmentioning
confidence: 97%
“…Several other pathogens have been associated with AIH. One of the first associations was from two studies in the 1980s, when measles virus (MV) was found in 12 of 23 patients and 12 of 18 patients who had been diagnosed with AIH . However, since the early 1980s the definition as well as the diagnostic tools for AIH have changed dramatically, and it is not clear if those patients would still be diagnosed with AIH today.…”
Section: Other Pathogensmentioning
confidence: 99%